2010
DOI: 10.1002/hep.23894
|View full text |Cite
|
Sign up to set email alerts
|

The fractalkine receptor CX3CR1 protects against liver fibrosis by controlling differentiation and survival of infiltrating hepatic monocytes

Abstract: Chemokines modulate inflammatory responses that are prerequisites for organ fibrosis upon liver injury. Monocyte‐derived hepatic macrophages are critical for the development, maintenance, and resolution of hepatic fibrosis. The specific role of monocyte‐associated chemokine (C‐X3‐C motif) receptor 1 (CX3CR1) and its cognate ligand fractalkine [chemokine (C‐X3‐C motif) ligand 1)] in liver inflammation and fibrosis is currently unknown. We examined 169 patients with chronic liver diseases and 84 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
206
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 34 publications
9
206
2
Order By: Relevance
“…However, previous studies in disease models of liver, CNS, gut, and arteriosclerotic vessels (74) demonstrated that CX 3 CR1 signaling increased rather than reduced the life span of macrophages. In contrast to these findings, one recent study reported increased macrophage numbers and liver fibrosis in CX 3 CR1-deficient mice after surgical bile duct ligation, a model that resembles UUO by being induced by mechanic tissue damage (50). The discrepancy between macrophage accumulation and decreased macrophage life span in that study was suggested to have resulted from the release of proinflammatory mediators from CX 3 CR1-deficient dying macrophages that attracted further profibrotic macrophages.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, previous studies in disease models of liver, CNS, gut, and arteriosclerotic vessels (74) demonstrated that CX 3 CR1 signaling increased rather than reduced the life span of macrophages. In contrast to these findings, one recent study reported increased macrophage numbers and liver fibrosis in CX 3 CR1-deficient mice after surgical bile duct ligation, a model that resembles UUO by being induced by mechanic tissue damage (50). The discrepancy between macrophage accumulation and decreased macrophage life span in that study was suggested to have resulted from the release of proinflammatory mediators from CX 3 CR1-deficient dying macrophages that attracted further profibrotic macrophages.…”
Section: Discussionmentioning
confidence: 64%
“…Also, CX 3 CR1 has been implicated in monocyte recruitment into inflamed tissues, like arteriosclerotic vessels (45), the listeria-infected spleen (46), the eye (47), in colitis models (28), or the skin (48). Furthermore, CX 3 CR1 may exert profibrotic functions (49)(50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…390439; MP Biomedicals, Solon, OH) (8). Biochemical assays and gene and protein expression studies were performed as described previously (8,24,25).…”
Section: Mouse Models and Phenotyping Analysesmentioning
confidence: 99%
“…30 Its role in aortic accumulation of other leukocytes has not been reported. Second, CX3CR1 inhibits apoptosis of smooth muscle cells 31 2/2 macrophages undergo excess cell death in hepatic fibrosis 36 and renal candidiasis 37 and fibrosis. 38 CX3CR1 is upregulated on T cells in inflammation, CX3CR1 protects T H2 and T H1 cells from apoptosis, and cytokine production is higher in CX3CR1 + than CX3CR1 -T H1 cells.…”
mentioning
confidence: 99%